Early planetesimal differentiation and late accretion shaped Earth’s nitrogen budget - Wenzhong Wang; Michael J. Walter; John P. Brodholt; Shichun Huang (Nature Communications, 2024)
Abstract The relative roles of protoplanetary differentiation versus late accretion in establishing Earth’s life-essential volatile element inventory are being hotly debated. To address this issue, we employ first-principles calculations to investigate nitrogen (N) isotope fractionation during Earth’s accretion and differentiation. We find that segregation of an iron core would enrich heavy N isotopes in the residual silicate, while evaporation within a H2-dominated nebular gas produces an enrichment of light N isotope in the planetesimals. The combined effect of early planetesimal evaporation followed by core formation enriches the bulk silicate Earth in light N isotopes. If Earth is comprised primarily of enstatite-chondrite-like material, as indicated by other isotope systems, then late accretion of carbonaceous-chondrite-like material must contribute ~ 30–100% of the N budget in present-day bulk silicate Earth. However, mass balance using N isotope constraints shows that the late veneer contributes only a limited amount of other volatile elements (e.g., H, S, and C) to Earth.